Establishing an importance-performance evaluating framework under integrating adaptive capacity for community-based plastic waste management - Thuy Phan, Thi Thanh; Nguyen, Van Viet; Lee, Chun-Hung (Frontiers in Environmental Science, 2023)
This study aims to conduct an importance-performance evaluation framework under the theoretical aspects of adaptive capacity for community-based plastic waste management (CBPWM). Additionally, we identified the matrix of the importance-performance levels of CBPWM, and estimated the community"s adaptive behavior towards CBPWM. The results indicate that residents highly have a high perceive perception of the importance of all adaptation indicators in CBPWM, but perceive poor performance in the indicators"ir implementation is plagued by poor performance. The respondents emphasize the significance of several adaptation indicators that can enhance the adaptive capacity for CBPWM, namely "developing waste collection systems", "building connections between resident associations", "collaborating among stakeholder"s groups", "adopting a zero-waste lifestyle", and "empowering independent waste collectors". The study also reveals that socioeconomic, perceptual, and behavioral factors related to adaptation indicators impact residents' willingness to participate in CBPWM strategies. This study is valuable as a starting point for building community adaptive capacity for plastic waste management. It is relevant to addressing both current and future plastic pollution problems in Vietnam, as it is based on actual assessments of the community. Determining the importance and performance of adaptive indicators provides valuable insights for policymakers in developing mechanisms and promoting opportunities for CBPWM.